Impacto de la implementación de normas internacionales de información financiera para Pymes en la ciudad de Santa Marta (2024)
This document implements the implementation of the International Financial Reporting Standards (IFRS) for Small and Medium Enterprises (SMEs) in the city of Santa Marta, has generated a great impact on the local business environment. The aim of this study is to analyse in detail the effects of this transition on SMEs in Santa Marta, examining both the advantages and the problems faced by local businesses. Through a detailed analysis, it has shown that the implementation of IFRS for SMEs has increased transparency and comparability of financial information for businesses, which has increased investor confidence and facilitated access to financing under more favourable conditions. In addition, there has been increased competition between small and medium-sized enterprises (SMEs) in national and international markets. Finally, this project emphasizes the importance of knowing the impact on implementation of the International Standards (NIF) for SMEs in Santa Marta. As the companies continue to adapt the NIF for SMEs, it is essential to monitoring and support this process to maximize benefits and support this process to maximize benefits and overcome challenges.